Clinical behaviors of rare variants of papillary thyroid carcinoma are associated with survival: a population-level analysis - Jiang CH; Cheng T; Zheng XC; Hong SK; Liu S; Liu JJ; Wang J; Wang SY (Cancer Management and Research, 2018)
Chenghao Jiang,1,* Tong Cheng,2,* Xucai Zheng,1 Shikai Hong,1 Song Liu,1 Jianjun Liu,1 Jing Wang,1 Shengying Wang1 1Department of Head – Neck Surgery, Anhui Provincial Cancer Hospital, West Branch of Anhui Provincial Hospital, Hefei, China; 2Department of Endocrinology, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, China *These authors contributed equally to this work Objective: This study was to evaluate the risk factors of survival in patients with columnar cell variant (CCV) and encapsulated variant (ECV). Materials and methods: The Surveillance, Epidemiology, and End Results database (1988–2013) was used to compare the characteristics of CCV and ECV with those of classic papillary thyroid carcinoma (PTC). Survival was analyzed by the Kaplan–Meier method, the log-rank test, and Cox multivariate regression. Multivariate logistic regression was used to further analyze lymph node metastases and distant metastasis. There were 765 CCV, 529 ECV, and 39,035 PTC patients. ECV tumors were similar to PTC in terms of overall survival, disease-specific survival, age, sex, and distant metastasis. Results: Compared with PTC, CCV tumors tended to be larger, with a higher incidence rate among males and in patients ≥65 years of age. CCV was associated with higher rates of extrathyroidal extension, multifocality, lymph node examinations, and lymph node and distant metastases (p<0.0001). Significant differences were found in 10-year overall survival (97.14% vs 89.15%, p<0.0001) and disease-specific survival (99.08% vs 93.07%, p<0.0001) between PTC and CCV. In CCV, distant metastasis (hazard ratio 5.125, p<0.0001) and lymph nodal metastasis (hazard ratio 2.152, p=0.032) predicted a poor prognosis. After adjustment, distant metastasis was independently associated with age ≥65 years, and lymph nodal metastasis was independently associated with female sex (odds ratio [OR] 0.341 [0.234–0.496]), extrathyroidal extension (OR 2.453 [1.368–4.397]), multifocality (OR 2.168 [1.318–3.569]), size >20 mm, ≤40 mm (OR 1.851 [1.170–2.928]), and size >40 mm (OR 1.847 [1.088–3.136]). Conclusion: ECV appears to have a similar prognosis to PTC, while CCV has a worse prognosis than classic PTC. Treatment with external beam radiotherapy and radioactive implants should be conducted carefully in patients with CCV. Keywords: columnar cell, encapsulated variant, disease-specific survival, external beam radiotherapy, distant metastasis, SEER